Spatial Pattern Analysis of the Distribution of Public Secondary Schools in Metro City, Lampung Province - Nyokro Mukti Wijaya; Meri Herlina; Riki Tri Kurniawan; Angga Margianto (Indonesian Journal Publisher, 2025)
This study aims to analyze the spatial pattern of the distribution of public junior high schools (SMP) in Metro City as a basis for evaluating equitable access to education in urban areas. A quantitative approach was used with the Nearest Neighbor Analysis (NNA) method based on Geographic Information Systems (GIS). School location data was obtained from the Education Office and field mapping results, then analyzed using ArcGIS 10.8 software to calculate the spatial distribution index (T). The results showed that the 10 public junior high schools in Metro City were spread across five subdistricts with an even distribution pattern (T value = 1.8). These schools were generally located around collector road networks and residential centers, indicating a strong correlation between the location of educational facilities and factors of accessibility and population density. These findings indicate that local government policies have taken into account the principle of spatial justice in the provision of educational services. GIS-based spatial analysis has proven to be effective in evaluating the equitable distribution of educational facilities and can be used as a basis for planning new schools in potentially developing suburban areas. This study emphasizes the importance of integrating spatial planning and educational policy to achieve sustainable access equity. Keywords : Spatial Patterns; Junior High Schools; Educational Equity; Nearest Neighbor Analysis; GIS